Práticas seguras para prevenção de infecção na administração de injetáveis: conhecimento de profissionais de enfermagem - Jarina, Nathália Valentim (Universidade Federal de São Carlos, 2023)
Objective: To measure the knowledge of nursing professionals about safe practices to prevent infection in injectable drugs. Method: Descriptive, exploratory, using an online survey and a validated instrument between November 2021 and February 2022. 2022. Results: Among the 781 participants, 334 (42.8%) were nurses, 360 (46.1%) worked in hospitals and 724 (92.7%) belonged to the Southeast region. The average overall percentage of correct answers was 84.48%, with the domain "Disposal of sharps" having the lowest score (25%). lowest score (25%). Weaknesses include: the lack of mandatory antisepsis for intradermal and subcutaneous injection (28.8%) and the possibility of using vials in more than one patient, as long as they don't enter the patient, as long as it doesn't enter the patient's unit (35.3%). Conclusion: there are still weaknesses in relevant aspects associated with the risk of transmission of microorganisms in the administration of administration, reinforcing the need for educational actions to promote safe practices.
Safe practices for the prevention of infections in the administration of injectables: knowledge of nursing professionals
Keywords: Profissionais de enfermagem; Controle de Infecções; Injeções; Nursing team; Infection control; Injections; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE DOENCAS CONTAGIOSAS